2015
DOI: 10.1186/s13045-015-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA, GAS5, enhances gefitinib-induced cell death in innate EGFR tyrosine kinase inhibitor-resistant lung adenocarcinoma cells with wide-type EGFR via downregulation of the IGF-1R expression

Abstract: BackgroundEpidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are approved for patients with recurrent non-small cell lung cancer (NSCLC). However, the efficacy of EGFR-TKIs in NSCLC therapy is limited by primary and acquired resistance. Recent studies have revealed that long non-coding RNAs (LncRNA) may be involved in EGFR-TKI resistance. Therefore, a better understanding of the interactive mechanisms underlying LncRNA-mediated EGFR-TKIs resistance may help us to improve clinical response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 38 publications
1
119
1
Order By: Relevance
“…Disregulation of lncRNAs other than HOTAIR plays critical roles in EGFR-TKIs resistant NSCLC cells. The lncRNA-mediated EGFR-TKIs resistance might help us to improve clinical response rates and could be used as novel potential targets to reverse the EGFR-TKI resistance for NSCLC patients [45,46]. Our findings implied that targeting In addition, we demonstrated an important role of EZH2 in this process.…”
Section: Discussionmentioning
confidence: 56%
“…Disregulation of lncRNAs other than HOTAIR plays critical roles in EGFR-TKIs resistant NSCLC cells. The lncRNA-mediated EGFR-TKIs resistance might help us to improve clinical response rates and could be used as novel potential targets to reverse the EGFR-TKI resistance for NSCLC patients [45,46]. Our findings implied that targeting In addition, we demonstrated an important role of EZH2 in this process.…”
Section: Discussionmentioning
confidence: 56%
“…lncRNAs also take part in the regulation of EGFR-TKI resistance. GAS5, one lncRNA, was found to be overexpressed in EGFR-TKI-sensitive cells compared with its expression in resistant cells, and was found to enhance gefitinib-induced cell death in innate EGFR-TKIresistant LAC cells with wild-type EGFR via downregulation of IGF-1R expression (10). These findings indicate that lncRNAs may be promising biomarkers as diagnostic and therapeutic targets in the resistance of EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 83%
“…GAS5 could inhibit autophagy and therefore enhance cisplatin sensitivity in NSCLC cells [86]. Another study found that GAS5 overexpression was inversely correlated with EGFR pathway and the expression of IGF-1R proteins in human ADC cell line, indicating its role in reversing EGFR-TKIs resistance [87]. These indings indicate the tumour suppressor lncRNA GAS5 may represent a potential biomarker for diagnosis and therapy target for NSCLC intervention.…”
Section: Other Functional Lncrnas In Nsclcmentioning
confidence: 99%